High-cleanliness polyester master batch and preparation method thereof

By adding silica and other components to the polyester masterbatches used in food packaging, the problem that existing polyester masterbatches cannot effectively block light and other factors is solved, achieving high cleanliness and strong light shading effects, protecting Food quality.

CN119432019APending Publication Date: 2025-02-14JIANGSU SHUANGXING COLOR PLASTIC NEW MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411784923.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In food packaging applications, existing polyester masterbatches cannot effectively block light, moisture, oxygen and microorganisms, resulting in changes in food quality.

Method used

Prepare by adding silica (SiO2) as an opening agent to the BOPET production formula and premixing, stirring and melt extrusion with other components such as titanium dioxide, carbon black, light absorber and pentaerythritol stearate. High clean polyester masterbatch.

Benefits of technology

The mechanical properties, temperature resistance and light shading effect of the polyester masterbatch are improved, and the barrier ability to light is significantly enhanced, thereby protecting food quality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a high-cleanness polyester master batch, which is characterized in that silicon dioxide is used as an anti-blocking agent, and the high-cleanness polyester master batch is prepared by grinding, premixing and stirring silicon dioxide and BOPET (Biaxially Oriented Polyester Terephthalate), melting and extruding by mixing and granulating equipment, and granulating. According to the invention, the SiO2 component is added in the BOPET production formula, the mechanical property and temperature resistance of the product can be improved by adding SiO2, and the effect is more obvious compared with that of the nano-scale BOPET; pure PET is difficult to crystallize at a relatively high cooling speed, that is, the crystallization speed of the film can be improved by adding a proper amount of SiO2 master batch in the production of the polyester film, so that the mechanical property and the temperature resistance of the film are further improved; in addition, the titanium dioxide is added, so that the shading effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polyester masterbatch manufacturing, and in particular to a high-purity polyester masterbatch and a preparation method thereof. Background Art

[0002] Polyester masterbatch has different requirements in different occasions, especially in food packaging applications, where its light blocking properties and cleanliness must meet certain requirements. Food packaging must be protected from contamination by light, moisture, oxygen, and microorganisms during transportation and shelf life, which can lead to changes in food odor, color, and quality.

[0003] Therefore, a polyester masterbatch with high cleanliness must be developed to meet the demand. Summary of the invention

[0004] The object of the present invention is to provide a high-purity polyester masterbatch and a preparation method thereof to solve the above technical problems.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A high-clean polyester masterbatch, characterized in that silicon dioxide is used as an opening agent, and is ground with BOPET, premixed, stirred, melt-extruded through a mixing and granulating device, and pelletized to obtain the masterbatch.

[0007] The present invention also provides a method for preparing a high-purity polyester masterbatch, which is characterized by comprising the following steps:

[0008] S100, mixing the following components in weight ratio under an inert gas atmosphere,

[0009] PET 30-34%;

[0010] Titanium dioxide 55-60%;

[0011] Carbon black 0.05-0.1%;

[0012] Light absorber 0.2-0.4%;

[0013] Pentaerythritol stearate 0.4-0.5%;

[0014] Silicon dioxide 5-15%;

[0015] S200, after mixing, transfer to a high-speed mixer for high-speed stirring for a certain period of time. The stirring process is maintained in an inert gas atmosphere. Finally, the mixed material is transferred to a twin-screw machine for pelletizing.

[0016] The present invention is further arranged that the temperature of the twin-screw extruder is: 210°C, 220°C, 230°C, 240°C, 255°C, 260°C, 260°C, 260°C, 260°C, 260°C, and the head temperature is 260°C.

[0017] The present invention is further configured that, when extracting pellets, the length of the material strips passing through water is controlled to be at least 0.8 meters, and the prepared master pellets are crystallized at a temperature of 85-90° C. in a crystallization tank, and the crystallization time is at least 1.5 hours.

[0018] The present invention further provides that, in step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0019] PET 34%;

[0020] Titanium dioxide 55%;

[0021] Carbon black 0.1%;

[0022] Light absorber 0.4%;

[0023] Pentaerythritol stearate 0.5%;

[0024] Silicon dioxide 10%;

[0025] The present invention further provides that, in step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0026] PET 34%;

[0027] Titanium dioxide 60%;

[0028] Carbon black 0.1%;

[0029] Light absorber 0.4%;

[0030] Pentaerythritol stearate 0.5%;

[0031] Silicon dioxide 5%.

[0032] The present invention further provides that, in step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0033] PET 34%;

[0034] Titanium dioxide 58%;

[0035] Carbon black 0.1%;

[0036] Light absorber 0.4%;

[0037] Pentaerythritol stearate 0.5%;

[0038] Silicon dioxide 7%.

[0039] The present invention is further configured to control the water-passing length of the material strips to be 0.8-1.0 meters.

[0040] The present invention further arranges that the crystallization temperature of the crystallization tank is 90°C.

[0041] The present invention is further arranged that the crystallization time is 1.5-2 hours.

[0042] The beneficial effects of the present invention are as follows: the present invention adds SiO2 components to the BOPET production formula, and the addition of SiO2 can improve the mechanical properties and temperature resistance of the product, and the nano-level effect is more obvious in comparison; pure PET is difficult to crystallize at a higher cooling rate, that is, adding an appropriate amount of SiO2 masterbatch in the production of polyester film can increase the crystallization rate of the film, thereby further improving the mechanical properties and temperature resistance of the film; in addition, the present invention also adds titanium dioxide to improve the shading effect. DETAILED DESCRIPTION

[0043] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0044] A high-clean polyester masterbatch, characterized in that silicon dioxide is used as an opening agent, and is ground with BOPET, premixed, stirred, melt-extruded through a mixing and granulating device, and pelletized to obtain the masterbatch.

[0045] The present invention also provides a method for preparing a high-purity polyester masterbatch, which is characterized by comprising the following steps:

[0046] S100, mixing the following components in weight ratio under an inert gas atmosphere,

[0047] PET 30-34%;

[0048] Titanium dioxide 55-60%;

[0049] Carbon black 0.05-0.1%;

[0050] Light absorber 0.2-0.4%;

[0051] Pentaerythritol stearate 0.4-0.5%;

[0052] Silicon dioxide 5-15%;

[0053] S200, after mixing, transfer to a high-speed mixer for high-speed stirring for a certain period of time. The stirring process is maintained in an inert gas atmosphere. Finally, the mixed material is transferred to a twin-screw machine for pelletizing.

[0054] The present invention is further arranged that the temperature of the twin-screw extruder is: 210°C, 220°C, 230°C, 240°C, 255°C, 260°C, 260°C, 260°C, 260°C, 260°C, and the head temperature is 260°C.

[0055] The present invention is further configured that, when extracting pellets, the length of the material strips passing through water is controlled to be at least 0.8 meters, and the prepared master pellets are crystallized at a temperature of 85-90° C. in a crystallization tank, and the crystallization time is at least 1.5 hours.

[0056] The present invention further provides that, in step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0057] PET 34%;

[0058] Titanium dioxide 55%;

[0059] Carbon black 0.1%;

[0060] Light absorber 0.4%;

[0061] Pentaerythritol stearate 0.5%;

[0062] Silicon dioxide 10%;

[0063] The present invention further provides that, in step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0064] PET 34%;

[0065] Titanium dioxide 60%;

[0066] Carbon black 0.1%;

[0067] Light absorber 0.4%;

[0068] Pentaerythritol stearate 0.5%;

[0069] Silicon dioxide 5%.

[0070] The present invention further provides that, in step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0071] PET 34%;

[0072] Titanium dioxide 58%;

[0073] Carbon black 0.1%;

[0074] Light absorber 0.4%;

[0075] Pentaerythritol stearate 0.5%;

[0076] Silicon dioxide 7%.

[0077] The present invention is further configured to control the water-passing length of the material strips to be 0.8-1.0 meters.

[0078] The present invention further arranges that the crystallization temperature of the crystallization tank is 90°C.

[0079] The present invention is further arranged that the crystallization time is 1.5-2 hours.

[0080] The present invention adds SiO2 components to the BOPET production formula, and the mechanical properties and temperature resistance of the product can be improved by adding SiO2. In comparison, the effect of nanometer level is more obvious; pure PET is difficult to crystallize at a higher cooling rate, that is, adding an appropriate amount of SiO2 masterbatch in the production of polyester film can increase the crystallization rate of the film, thereby further improving the mechanical properties and temperature resistance of the film; in addition, titanium dioxide is added in the present invention to improve the shading effect, and its experimental test is as follows:

[0081] Embodiment 1:

[0082] In step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0083] PET 34%;

[0084] Titanium dioxide 55%;

[0085] Carbon black 0.1%;

[0086] Light absorber 0.4%;

[0087] Pentaerythritol stearate 0.5%;

[0088] Silicon dioxide 10%;

[0089] Embodiment 2: In step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0090] PET 34%;

[0091] Titanium dioxide 60%;

[0092] Carbon black 0.1%;

[0093] Light absorber 0.4%;

[0094] Pentaerythritol stearate 0.5%;

[0095] Silicon dioxide 5%.

[0096] Embodiment 3:

[0097] In step S100, the following components in weight ratio are mixed under an inert gas atmosphere:

[0098] PET 34%;

[0099] Titanium dioxide 58%;

[0100] Carbon black 0.1%;

[0101] Light absorber 0.4%;

[0102] Pentaerythritol stearate 0.5%;

[0103] Silicon dioxide 7%.

[0104] Test method:

[0105] In the present invention, the polyester masterbatch is prepared using the components of Example 1, and the specific method is as follows:

[0106] The following weight ratios of components were mixed under an inert gas atmosphere:

[0107] PET 34%;

[0108] Titanium dioxide 55%;

[0109] Carbon black 0.1%;

[0110] Light absorber 0.4%;

[0111] Pentaerythritol stearate 0.5%;

[0112] Silicon dioxide 10%;

[0113] After mixing, the mixture is transferred to a high-speed mixer and stirred at high speed for a certain period of time. The stirring process is maintained in an inert gas atmosphere, wherein nitrogen is used as the inert gas. Finally, the mixed material is transferred to a twin-screw extruder for pelletizing.

[0114] The temperature of the twin-screw extruder is: 210℃, 220℃, 230℃, 240℃, 255℃, 260℃, 260℃, 260℃, 260℃, 260℃, and the head temperature is 260℃. When extracting the pellets, the length of the material strip passing through the water is controlled to be 0.8 meters. The prepared masterbatch is crystallized at 90℃ in the crystallization tank for 1.5 hours. The prepared masterbatch is dried and diluted to form masterbatch with different step contents. The dilution ratio is 5%, 10%, 15% and 20%, and it is made into standard specimens to test its physical properties. The injection molding temperature of the standard sample strips is 260℃. The prepared sample strips are naturally cooled for 24 hours and then tested for their performance.

[0115] The color light test of the material adopts D65 light source and 10° reflected light source. Each formula is tested for 10 sets of data and the results are averaged.

[0116] The following results are obtained, as shown in Table 1;

[0117] Table 1 Effect of different proportions of addition on product cleanliness and light blocking

[0118] Proportion 0% 5% 10% 15% 20% Cleanliness - 89.23% 92.37% 94.88% 98.31% Coverage 5.21% 96.36 97.33 98.79 99.32

[0119] Table 1 is a test of light blocking with different proportions of masterbatch addition. From the table, we can see that as the proportion increases, the material's light blocking becomes stronger and stronger. This is mainly because as the amount of masterbatch added increases, the titanium dioxide content and ultraviolet light absorber content in the system also increase. Titanium dioxide in titanium dioxide has a reflective and refracting effect on light. As the content increases, titanium dioxide is distributed more and more densely, and the reflection and refraction of light are stronger, and the coverage is higher. Even if some light is not reflected and refracted, it will be absorbed by the ultraviolet light absorber, and even less light can penetrate the packaging, and the impact on the contents can be ignored. At the same time, the presence of graphene improves the cleanliness of the product. In addition, since the mixing and stirring are carried out in an inert gas atmosphere, the mixing of impurities is avoided, further improving the cleanliness.

[0120] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different terms to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. For example, "including" mentioned throughout the specification and claims is an open term, so it should be interpreted as "including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve technical problems within a certain error range and basically achieve technical effects.

[0121] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0122] The above description shows and describes several preferred embodiments of the present invention, but as before, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept of this article through the above teachings or the technology or knowledge of the relevant field. And the changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A high-purity polyester masterbatch, characterized in that: Silica is used as an opening agent and is ground, premixed, stirred and melt-extruded with BOPET through a mixing and granulation equipment. It is obtained by granulation.

2. A method for preparing high-purity polyester masterbatch, characterized in that: The steps include: S100, mixing the following components in weight ratio under an inert gas atmosphere, PET 30-34%; Titanium dioxide 55-60%; Carbon black 0.05-0.1%; Light absorber 0.2-0.4%; Pentaerythritol stearate 0.4-0.5%; Silicon dioxide 5-15%; S200, after mixing, transfer to a high-speed mixer for high-speed stirring for a certain period of time. The stirring process is maintained in an inert gas atmosphere. Finally, the mixed material is transferred to a twin-screw machine for pelletizing.

3. The method for preparing a high-purity polyester masterbatch according to claim 2, characterized in that: The temperatures of the twin-screw extruder are: 210°C, 220°C, 230°C, 240°C, 255°C, 260°C, 260°C, 260°C, 260°C, and the head temperature is 260°C.

4. The method for preparing a high-purity polyester masterbatch according to claim 2, characterized in that: When extracting pellets, control the length of the material strips passing through water to be at least 0.8 meters. The prepared masterbatch is crystallized in a crystallization tank at 85-90°C for at least 1.5 hours.

5. The method for preparing a high-purity polyester masterbatch according to claim 2, characterized in that: In step S100, the following components in weight ratio are mixed under an inert gas atmosphere: PET 34%; Titanium dioxide 55%; Carbon black 0.1%; Light absorber 0.4%; Pentaerythritol stearate 0.5%; Silicon dioxide 10%.

6. The method for preparing a high-purity polyester masterbatch according to claim 2, characterized in that: In step S100, the following components in weight ratio are mixed under an inert gas atmosphere: PET 34%; Titanium dioxide 60%; Carbon black 0.1%; Light absorber 0.4%; Pentaerythritol stearate 0.5%; Silicon dioxide 5%.

7. The method for preparing a high-purity polyester masterbatch according to claim 2, characterized in that: In step S100, the following components in weight ratio are mixed under an inert gas atmosphere: PET 34%; Titanium dioxide 58%; Carbon black 0.1%; Light absorber 0.4%; Pentaerythritol stearate 0.5%; Silicon dioxide 7%.

8. The method for preparing a high-purity polyester masterbatch according to claim 4, characterized in that: Control the length of the material strip passing through water to 0.8-1.0 meter.

9. The method for preparing a high-purity polyester masterbatch according to claim 5, characterized in that: The crystallization temperature of the crystallization tank is 90°C.

10. The method for preparing a high-purity polyester masterbatch according to claim 5, characterized in that: The crystallization time is 1.5-2 hours.

Citation Information

Cited By

  • Polyester barrier material for food packaging as well as preparation method and application of polyester barrier material

    CN121628318A